Limestone Waste ? an Effort towards Protection of the Envi-ronment - I. L. Grigorova (International Mineral Processing Congress, 2014)
As a result of the main processes of the limestone treatment ? sawing, buffing and polishing, a technological waste is usually obtained. These final tailings consist of a water suspension with highly variable solid phase content and granulometric composition. Since the waste is conducted to a tailing pool or another place, this leads to environment pollution. In this work the slurry waste generated during the limestone processing in a Bulgarian limestone manufacturing company was characterized. The chemical composition, particle size distribution, solid phase content, whiteness, yellowness, abrasion, specific surface and density were determined. The possibility of obtaining building/construction materials from limestone processing waste was studied in a laboratory scale. The technological tests included thickening, filtration and drying of waste products. Continuous operation laboratory thickener was used. Coagulant Accepta® 8302 (aluminum sulphate solution) and anionic flocculant Magnafloc® 155 were found to be the most effective in the sedimentation of the products. Filtration tests were performed using a laboratory pressure filter. Drying tests were carried out in laboratory facilities using the direct heating method. On the basis of the laboratory results a technology for limestone treatment waste was developed. A production line for building materials from limestone slurry was set up. As a result the manufacturing company has a possibility to use circulating water.